Bioaccumulation of Heavy Metals by Acanthus ilicifolius in Polluted Mangrove Ecosystems - Etti Sartina Siregar; Erni Jumilawaty; Masitta Tanjung; Ade Syafitri; Cecep Kusmana; Mohammad Basyuni; Adrian Hartanto; Rinny Rahmania (Emerging Science Journal)
Mangrove forests in Sicanang Belawan, North Sumatra, covering 1,510 hectares, are essential for coastal ecosystem services, such as silvofishery and polyculture ponds. Despite their potential, heavy metal pollution has emerged due to anthropogenic activities upstream. Therefore, this study aims to determine the bioaccumulation and translocation capacities of Acanthus ilicifolius for copper (Cu), lead (Pb), and zinc (Zn). Samples were collected from 4 sites, representing varying pollution levels, namely Station 1 (mangrove ecotourism area), Station 2 (control site), Station 3 (industrial area with power plant activities), and Station 4 (industrial site near manufacturing facilities). Atomic absorption spectroscopy (AAS) was then used to measure metal concentrations in sediments and plant tissues (roots, stems, and leaves). The results showed that there were significant site-specific differences in Cu and Pb levels, while Zn concentrations had no significant variation. A. ilicifolius exhibited the highest bioconcentration factor for Cu at Station 1 (2.43±0.76 ppm), while extreme translocation of Pb to leaves was observed at the same location (9.21 ppm). Despite moderate Pb toxicity at Station 1, overall sediment contamination was considered low. This is the first study reporting heavy metal contamination in Sicanang mangrove, identifying A. ilicifoliusas an effective phytoremediator for Cu, Pb, and Zn, aiding pollution mitigation in mangrove ecosystems.